Assessment of soluble ST2 as a novel cardiac biomarker in cats with cardiomyopathy - Yasemin KAYA; Utku BAKIREL (German Journal of Veterinary Research)
Soluble suppression of tumorigenesis-2 (sST2), a member of the interleukin-1 receptor family, is a novel biomarker of mechanical stress that is measurable in serum. It has been shown in humans and animals to be physiologically related to cardiac hypertrophy, fibrosis, and ventricular dysfunction. This study aimed to evaluate sST2 levels in cats with cardiomyopathy. In addition, serum sST2 and other cardiac biomarker levels were compared. Twenty-four client-owned cats with hypertrophic cardiomyopathy (HCM) and restrictive cardiomyopathy (RCM) were investigated. The cats included in the study were divided into four groups (I, II, III, and IV) according to the American College of Veterinary Internal Medicine (ACVIM) classification. Class B1 cats were included in group I (n=7), class B2 cats were included in group II (n=6), class C cats were included in group III (n=6), and healthy control-group cats in group IV (n=5). Measurement of cardiac troponin I (cTnI), cardiac troponin T (cTnT), N-terminal pro-brain natriuretic peptide (NT-proBNP), creatine kinase-MB (CK-MB), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), sST2 levels, and echocardiographic examinations were performed in all groups, and correlations were investigated. We observed positive correlations among sST2 levels and CK-MB and LA diameter (p=0.05). There was no correlation between sST2, NT-proBNP, Troponin I, Troponin T, AST, and LDH levels. We confirmed positive correlations between NT-proBNP levels and LA diameter (p